EFL Learners' Preferences for Multimodal Learning Materials at the Secondary School Level - Pratiwi, Dian; Trisanti, Novia (Journal of English Language and Education, 2025)
This study explores secondary school EFL learners' preferences for multimodal learning materials, which addresses the need for learner-centered strategies in 21st century education. Although existing research highlights the general benefits of multimodal teaching, few studies have examined students' specific preferences for text, audio, and video formats. Using a quantitative descriptive design, data was collected from 132 junior high school students in Indonesia through a VARK-based questionnaire and Likert-scale items. The results showed that video was the most preferred medium (50.8%), followed by text and audio. Students reported that video materials were more engaging and effective in improving comprehension and motivation. Although the VARK model provides background insights, this study shows that learners' actual media choices have more influence on instructional design. This demands the use of multimedia resources that reflect students' preferences and enhance engagement in EFL learning.